Systematic Literature Review: Online Food Delivery Purchasing Decisions in Indonesia - Bagus Hary Prastito; Yunia Wardi (Journal of Social Research, 2024)
Previous research is very fundamental in supporting a scientific work or scientific article. With the existence of previous research, it is useful to strengthen the theory and phenomenon of the relationship of each existing variable. This data collection requires a comprehensive literature search. The method used in this research is systematic literature review (SLR), which is a systematic literature review that aims to identify, evaluate, and interpret the results of primary research. This study investigates purchasing decisions, service quality, advertising, and price among online food delivery app users in Indonesia. The purpose of this paper is to review the aspects that in this case affect purchasing decisions; namely: service quality, promotion, and price. This research aims to create hypotheses between each variable that can be used for further research. The results of this literature review research are: 1. Service quality affects purchasing decisions. 2. Promotion affects purchasing decisions. 3. Price affects purchasing decisions.